GRAMMATICAL REALIZATION OF BLESSINGS, CURSES AND WISHES IN ENGLISH AND UZBEK LANGUAGES - Jurabekova Feruza Jura kizi (Modern American Journals, 2025)
This article explores the grammatical structures that underpin the expression of blessings, curses, and wishes in English and Uzbek languages. By analyzing sentence mood, verb forms, syntactic construction, and morphological features, the study identifies the typological and functional parallels and divergences between these two languages. Blessings and wishes are often realized through optative and imperative moods, while curses frequently involve negation and intensified modality. The study highlights how culturally embedded ritual expressions rely on distinct grammatical choices that reflect each language’s communicative norms and socio-cultural values.
Keywords: blessings, curses, wishes, grammar, syntax, sentence mood, modality, Uzbek, English, typology, ritual speech acts